(untitled) (Research, Society and Development, 2021)
The irregular discharge of effluents containing dyes causes degradation of the water body. The objective of this research is to manufacture activated charcoal through the cashew nut mesocarp (Anacardium occidentale) for water treatment, by means of adsorption, in order to remove the dye Malachite Green. 1 kg of residual cashew nut biomass was collected in a cooperative in the municipality of Ipixuna-PA, followed by a chemical activation process with sodium hydroxide (NaOH). The sample was characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (ATG), textural analysis (SBET), Scanning Electron Microscopy (SEM / EDS). Regarding the treatment of the water containing the dye, studies were carried out for Equilibrium and adsorption kinetics. In this sense, for equilibrium, they were adjusted to the Freundlich and Langmuir isotherms, while for the kinetics they were the Pseudo-First Order, Pseudo-Second Order and Intraparticle Diffusion models. FTIR results indicated the existence of hydroxyl (OH) and carboxyl (−COOH) functional groups. The SEM / EDS indicated solid particles stacked and agglomerated, generating aggregates of irregular morphology, mainly revealing the elements: Oxygen (O = 46.94%), Carbon (C = 34.66%); Sodium (Na = 16.13%). As for adsorption, the Langmuir model was adjusted for equilibrium (R²adj = 0.8487; Qmax = 573.83mg / g -1) and favorable adsorption with RL = 0.0013. On the other hand, in kinetics, intra-particle diffusion was adjusted (R² adj = 0.9966; C = 69.13 mg / g-1). Therefore, activated carbon has demonstrated effectiveness in removing the dye due to the influence of functional organic groups, which favor the interaction of cationic molecules.